Association between gamma glutamyl transpeptidase to HDL-Cholesterol (GGT/HDL-C) ratio and metabolic syndrome resolution after sleeve gastrectomy - Lizarbe-Lezama, Melanni L. (2024)
Objective: To evaluate the association between GGT/HDL-C ratio and resolution of MetS in adults after sleeve gastrectomy (SG). Methods: We conducted a retrospective cohort study using secondary data from a Peruvian bariatric center. The study population consisted of adults aged 18 and above who underwent laparoscopic SG and were diagnosed with MetS prior to the surgery. The main outcome measured was MetS resolution 6 months post-surgery and the exposure variable was the GGT/HDL-C ratio. Results: We analyzed 137 patients with a mean age of 38.9 ± 10.9 years; 64.2% were females. The median GGT/HDL-C ratio was 1.1 [0.7 – 1.5], and 83.9% of patients experienced resolution of MetS. Furthermore, both the middle tertile of GGT/HDL-C (aRR: 1.28; 95% CI: 1.04 - 1.58; p =.019) and the lowest tertile (aRR: 1.27; 95% CI: 1.01 - 1.60; p =.038) showed a significant association with the resolution of MetS. Conclusion: Eight out of 10 patients undergoing SG experience resolution of MetS within 6 months after surgery. Patients in the middle and lower tertiles of the GGT/HDL-C were more likely to achieve this outcome. Therefore, the GGT/HDL-C ratio should be considered a valuable and efficient biomarker for preoperative assessment of bariatric surgery candidates.